Faktor-faktor yang berhubungan dengan kejadian GAKY pada anak sekolah dasar di pinggiran pantai Kota Palu Provinsi Sulawesi Tengah - Normawaty Patuti; Toto Sudargo; Deddy Nur Wachid (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2010)
Background: Iodine deficiency disorder (IDD) is one of serious health problems considering that it has great impact to survival and quality of human resources. The core problem of IDD is initially caused by lack of iodine in water and soil, then heightened by goitrogenic substances in the food consumed, more pollutants as side effects of industrial waste, the blocking agent which naturally exists in water and soil in the surrounding dwelling places.Objective: The study aimed to identify factors affecting the prevalence of IDD among elementary school children at coastal region.Method: The study was analytic observational with cross sectional design. Population and samples of the study were elementary school children of grade 4-6 proportionally chosen that fulfiled inclusion criteria. Variables observed were consumption pattern, environment (drinking water plumbum), and children’s hemoglobin. Data analysis used computer software at signifiance level p<0.05 and confience interval 95% and estimation of risk level (Odds Ratio) with chi square. The result of analysis was presented in frequency distribution table and percentage. Analysis of food nutrient was done with recall 24 hours, dietary history. Examination was made to thyroid gland palpation and hemoglobin using cyanomethemoglobin and drinking water plumbum using Atomic Absorption Spectrophotometer.Result: The result of independent and dependent statistical test showed that there was signifiant effect of consumption pattern of protein source to the prevalence of IDD (p<0.05), iron source to the prevalence of IDD (p<0.05), zinc source to the prevalence of IDD (p<0.05), iodine source to the prevalence of IDD (p<0.05) and hemoglobin source to the prevalence of IDD (p<0.05). Meanwhile, there was no effect of source goitrogenic (thiocyanate) to the prevalence of IDD (p>0.05), drinking water plumbum level to the prevalence of IDD (p>0.05).Conclusion: There was signifiant effect of consumption pattern of protein, iodine and hemoglobin level to the prevalence of IDD among elementary school children at coastal region of Palu Municipality. There was no effect of drinking water plumbum level to the prevalence of IDD among elementary school children at coastal region of Palu Municipality.